Celebrity Endorsement and the Buying Behavior in Consumers of Nepal - Upadhyay, Jitendra Prasad; Singh, Sanju Kumar (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The main objective of the study is to analyze the influence of celebrity endorsement on consumers’ buying behavior. Celebrity endorsement is considered the most effective tool to influence the customers’ buying behavior and motivate them to get attention towards the products produced by the company and services provided by the company. Due to the specific nature of research objectives, descriptive and causal comparative research design has been used. Celebrity endorsement has higher impact on Consumer Buying Behavior of Nepal. In this research descriptive and causal comparative research design has been used. The study focuses on understanding the consumers buying behavior based on different factors like gender, income, occupation and education. Population of this research is total youth of Nepal and out of total population a sample size of 384 respondents is taken using the convenience sampling technique which consists of people from different age group, gender, income, occupation. The results of this study indicated that there was a positive impact of celebrity trustworthiness, features of products and attractiveness on consumer buying behavior. Moreover, results showed that most of the consumers agreed that celebrity endorsers enhanced brand awareness.